Association between Facebook Use, Depression and Family Satisfaction: A Cross-Sectional Study of Romanian Youth - Mihai Bogdan IOVU; Remus RUNCAN; Patricia-Luciana RUNCAN; Felicia ANDRIONI (Tehran University of Medical Sciences, 2020)
Background: In recent years, Facebook has increasingly become an essential part of the lives of people, particularly youths, thus many research efforts have been focused on investigating the potential connection between social networking and mental health issues. This study aimed to examine the relationship between Facebook use, emotional state of depression, and family satisfaction. Methods: This study used the online survey created in Google Docs on the Facebook 'wall', as research method. The survey was available during Jun-Jul 2015 in Romania. In our cross-sectional study on a sample of 708 young Facebook users (aged 13-35), we divided the sample into 3 groups: ordinary, middle, and intense Facebook users. Materials and instruments: the survey comprised a series of basic demographic as well as some measures of Facebook addiction, depression, and family satisfaction. We used two methods connected with extensive Facebook usage, the first one measuring only the intensity of use, and the second one measuring not only the intensity but also the consequences of this use. Results: Facebook engagement is negatively related to family satisfaction. Moreover, Facebook engagement is positively related to depression symptoms. The Pearson correlations showed that higher Facebook intensity is positively associated with Facebook addiction. Conclusion: The study confirm previously published findings of other authors in the fields of social networking psychology. The study examined the relationship between Facebook use, depression, and life satisfaction and the hypotheses were supported.